Influence of geological factors on surface deformation due to hydrocarbon exploitation using time-series InSAR: A case study of Karamay Oilfield, China - Xu, Lei; Yang, Yongpeng; Ju, Xing; Yang, Jinzhong (Frontiers in Earth Science, 2023)
Surface deformation due to hydrocarbon extraction from buried reservoirs may gradually evolve to geological hazards, which can undermine the safety of infrastructure facilities. Monitoring the surface deformation and studying on the influencing factors of surface deformation have great significance to ensure the stability of oilfield development, and prevent geological hazards. In this study, Sentinel-1 interferometric synthetic aperture radar (InSAR) data of Karamay Oilfield acquired between January 2018 to December 2020 was used to map how the land surface has deformed in response to hydrocarbon exploitation. Based on the monitoring results of time series InSAR, geological data, and oilfield data, the correlations between the different factors and the surface deformation were analyzed. The results show that the reservoir buried depth, porosity and permeability have an impact on the surface deformation, and the influence on surface uplift is obviously greater than that on surface subsidence. Surface uplift decreases with the increasing buried depth and the decreasing porosity and permeability, and the correlation between porosity and surface uplift is the best. However, the impact is limited in the area with shallow reservoir depth, high porosity, and high permeability, such as the heavy oil blocks in the study area.